(untitled) (De Rebus Antiquis, 2020)
The aim of this paper is to analyze the political metaphor known as pólis tÁ½rannos coined by Thucydides (II. 63. 2). We are starting from a brief analysis about the archaic tyranny and its evolution as a political and ideological concept in order to explain the origin and the basis of the analogy. Finally, we will analyze the metaphor in relation to the antidemocratic discourse of the Athenian aristocracy.